Optimization of data center cooling efficiency using reduced order flow modeling within a flow network modeling approach. (September 2017) - Fouladi, Kamran; Wemhoff, Aaron P.; Silva-Llanca, Luis; Abbasi, Kayvan; Ortega, Alfonso
Abstract: Much of the energy use by data centers is attributed to cooling, so improving the thermal management of data centers can translate to direct and significant economic benefits. However, data centers are complex systems that contain a significant number of components or sub-systems (e.g., servers, fans, pumps, and heat exchangers) that must be considered in any synergistic data center thermal efficiency improvement effort. In this paper, we demonstrate a novel hybrid modeling strategy for efficient and accurate second-law efficiency optimization of a data center cooling system using a proper orthogonal decomposition (POD) airflow modeling scheme with flow network modeling for external components. This strategy is applied to a data center cell, demonstrating energy and exergy savings of up to 23% and 43%, respectively, for a data center with large server utilization.